A Review of the Robotic Process Automation's Impact as a Disruptive Innovation in Accounting and Audit - et. al., Joydeep Mookerjee, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Robotic Process Automation (RPA) is a holistic approach to accounting and auditing processes that have made them more dynamic, secure, and safe. This study demonstrates the principle of robotic process automation (RPA) and how it impacts accounting processes. This review paper makes recommendations for future studies. An analysis of the literature from previous research as well as the most recent sources was conducted to identify research gaps. The study's results revealed the ability for RPA to automate accounting processes and the fact that robotic approaches are projected to replace accountants for a significant portion of their work. This will lead to a reduction in the number of base-level accounting roles. While also making it easier to create new accounting vacancies. Financial reporting for company consultancy and the transformation of robotic process automation would be among the future accountant's tasks.